Application of the RADEC Learning Model through the Experimental Method on Students' Critical Thinking Ability in Natural Science Learning Animal Movement Organ Material Class V SDN 13 Singkawang - Afriani, Rindi; Triani, Susan Neni; Utama, Erdi Guna (Jurnal Pendidikan Amartha, 2024)
This research aims to: 1) To describe the differences between the RADEC learning model through the experimental method on the critical thinking abilities of students who study with the RADEC learning model and classes that use direct learning in class V science learning at SDN 13 Singkawang; 2) To describe the implementation of the RADEC learning model through the experimental method on the critical thinking abilities of class V students at SDN 13 Singkawang in science learning; 3) To describe students' responses to the RADEC learning model through experimental methods on students' critical thinking abilities. This research is a quantitative experimental research. This research method is a quasi experimental design, with a post-test only control group design. The population of this study was all fifth grade students, totaling 50 students. Samples were taken using probability sampling techniques with saturated sampling. Data collection techniques use test and non-test techniques. The test instrument is a critical thinking ability question sheet in the form of an essay. Meanwhile, non-tests are in the form of model implementation observation sheets and student response questionnaire sheets. The data analysis technique used was a two-sample t test. The results of the research, 1) show that tcount = 3.844 ttable = 2.010, which means that there is a significant difference in the results of students' critical thinking ability tests between students who applied the RADEC model through the experimental method and students who used the direct learning model. 2) The results of the model implementation analysis show a percentage of 90.5%, very good criteria and 3) the results of the analysis of student response questionnaires show a percentage of 75% good criteria, which means that learning using the RADEC learning model through the experimental method in science learning has an effect on critical thinking skills. students' science, so that students respond well to learning activities. So it can be concluded that the RADEC learning model during the learning process makes an impression, attracts students' attention, and provides a new learning atmosphere